The gurubook : insights from 45 pioneering entrepreneurs and leaders on business strategy and innovation - Løw, Jonathan, 1978- (CRC Press, Taylor & Francis Group, 2018)
The GuruBook is an inspiring collection of 45 articles and interviews with well-known thought leaders and entrepreneurs, whose leadership and strategic skills have resulted in very successful businesses. These renowned leaders, entrepreneurs, and innovators have tested their visions and assumptions and have forged revolutionary business models. In this book, they share their most important insights, learnings, and tools. They cover broad topics such as entrepreneurship, innovation, and leadership, and they illustrate why these are not separate topics, but indeed must be combined and linked to succeed as a business and as an entrepreneur. The GuruBook was published in Scandinavia in the Autumn of 2016 and was an instant #1 bestseller. This English version of the book contains many additional exciting interviews with thinkers such as Salim Ismail (Singularity University), Naveen Jain (Moon Express), Jimmy Maymann (Huffington Post), Otto Scharmer (Theory U), Blake Mycoskie (TOMS) and many others. The GuruBook is for burgeoning entrepreneurs, leaders, business developers, and innovators who know that traditional business models no longer provide results in fast-evolving digital and global economies. Other contributing authors to the book include Simon Sinek, Seth Godin, Steve Blank, Sonia Arrison, Daniel Burrus, Edgar H. Schein, Henry Mintzberg, Tom Peters, Pascal Finette, Andreas Ehn, Murray Newlands, Brian Chesky, Hampus Jakobsson, Craig Newmark, Danny Lange, Alf Rehn, Paul Nunes, Nathan Furr and Mette Lykke. More information can be found at: www.thegurubook.org.